Study of aetiology and clinical spectrum of patients with acute undifferentiated fever, in a tertiary care setting: a descriptive cross-sectional study - Jishtu, Vinay; Jaret, Pramod K.; Machhan, Prem Chand; Chauhan, Nidhi (International Journal of Advances in Medicine, 2021)
Background: Acute undifferentiated fever illness (AUFI) is a common cause of morbidity and mortality in developing countries, owing to its non-specific features. The aim of the study was to delineate the causes and clinical parameters associated with AUFI. Methods: A cross-sectional study was done among 156 patients of AUFI, admitted in the Department of Medicine, Indira Gandhi Medical College, Shimla, Himachal Pradesh, India, from November 2018 to October 2019. Results: The mean age of the study participants was 37.37±14.2 years. The study participants admitted for acute undifferentiated febrile illness had fever with mean duration of 8.38±3.7 days before hospitalization. The most common aetiology of AUFI was found to be enteric fever (44%), followed by scrub typhus (35%). The majority of the cases presented from the month of September to December. Conclusions: The aetiology and clinical spectrum of AUFI is wide and variable. To outline a proper algorithm to contain it, meticulous analysis of the hospital data at each level is necessary.